طرق الكشف عن التفريق اللغوي من المأثورات التفسيرية: سورة يس نموذجاً = Methods for discovering linguistic differentiations in tafsir traditions: Surah Yasin as a sample - Saleem, Wahab; Elatrash, Radwan Jamal Yousef (IIUM Press, 2024)
التفريق اللغوي من أهم المناهج التفسيرية التي اعتمد عليها المفسرون في الصدر الأول، وبنى أئمة التفسير عليه كثيرًا من التأويلات، فكان للفروق اللغوية حضور يلاحظه من تأمل في تفاسير الصحابة والتابعين ومن بعدهم، وإلى هذا تهدف المقالة فإن مشكلتها تكمن في أن هذا المنهج لا يزال مغمورًا بين الباحثين، فهو بحاجة إلى مزيد إعزاز وإبراز، وقد أدى هذا الغمور ببعضهم إلى زعم أن الاعتماد على الفروق اللغوية في التفسير منهج دخيل على مناهج التفسير المعتبرة، وأنه ليس له طرق واضحة المعالم، ومن ثم فإن هذه الدراسة خُصِّصَتْ لبيان طرق الكشف عن الفروق اللغوية خلال النظر فيما نقل عن مفسري الصدر الأول؛ والمنهج المتبع في هذه الدراسة هو المنهج الاستقرائي التحليلي؛ مقتصرًا على الفروق المأثورة في تفسير سورة «يس»؛ وقد تضمنت هذه الدراسة معايير مفيدة للتفريق اللغوي من تراث أبي هلال العسكري التي ذكرها في كتابه الماتع «الفروق اللغوية»، كما أن الدراسة خلصت إلى طرق كاشفةٍ للفروق اللغوية، وقد ركزت على بيان أن التفسير بالفروق اللغوية منهج من مناهج الصدر الأول من الصحابة والتابعين وأتباع التابعين، واستعرض البحث كل الفروق المأثورة من تفسيرات الأجيال الثلاثة فيما ورد عنهم في تفسير سورة «يس»، كما تناول فرقًا واحدًا لم يتعرض له المفسرون الأوائل تنبيهًا على أن هذا الباب لا يزال مفتوحًا، وقد كان مجموع الفروق اللغوية المأثورة في تفسير سورة «يس» ستة فروق لغوية لها مدلولاتها البيانية المعتبرة عند المفسرين والبيانيين. ***** Linguistic differentiation is of the most important exegetical approaches that commentators relied on in the early generation. Exegetes based many interpretations on this approach. Thus, this approach had great presence in the interpretations of the companions, their follower, and those after them. This article aims to elucidate this approach as it still remains obscure among researchers. Its obscurity has led some to claim that relying on linguistic differences in interpretation is foreign to the reliable methods of interpretation, and that it does not have a clear process. Therefore, this study was dedicated to illustrating the methods of detecting linguistic differences while considering what was reported from the commentators of the early period. The methodology adopted in this study is the inductive analytical approach. It focuses solely on the differences mentioned in the tafsīr of Surah Yāsīn. This study includes useful criteria for linguistic differentiation from the work of Abū Hilāl Al-ʿAskarī, as found in his insightful book al-Furūq al-Lughawiyyah. The study also concluded with methods for the discovery of linguistic differences while emphasizing that tafsīr through these linguistic nuances is an early method employed by the Companions, their Followers, and those who followed them. The research reviewed all the differences reported from the tafsirs of these three generations within the scope of Sūrah Yāsīn. It also addressed one difference that the early commentators did not touch upon, indicating that this area remains open for exploration. The total number of linguistic differences reported regarding the interpretation of Sūrah Yāsīn was six differences, each with its significant linguistic implications considered by commentators and rhetoricians.